Identification Of Palm Using Otsu Method and Mathematical Morphology to Open House Doors Identifikasi Telapak Tangan Menggunakan Metode Otsu Dan MorphologynMatematika Untuk Membuka Pintu Rumah - Mahdiasa Sholihin; M. Arif; M.Hafiz Alfansury; Nindi Misyahdul Yuzi; Sumijan (Jurnal KomtekInfo, 2020)
The biometrics system is an individual recognition technology using human body parts or behavior. Palm and fingerprints, each biometrics example based on body parts and human behavior. Image matching is a way to identify images. This research uses biometric technology, a system that performs image matching based on human body parts by matching test images received with training images contained in a database. The image used is the palm of the hand. The use of the palm because the palm has unique characteristics, is difficult to fake and tends to be stable. There are 10 samples of the palm image that will be used using the Otsu method and the Math Morphology method, which were previously filtered using a median filter and turned into grayscale. From 10 different samples showing different results with an average similarity level of 96.28%, the method proves that the palm joints are a characteristic that is owned by everyone, and it also proves that the palm can also used as an alternative to protect privacy, not just fingerprints for home security.